Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
2x - 138 = 2^3 * 3^2 => 2x - 138 = 8 * 9 => 2x - 138 = 72 => 2x = 72 + 138 => 2x = 200 => x = 200 : 2 => x = 100
16 * 4^x = 48 => 4^x = 48 : 16 => 4^x = 3 => Chịu
Ta có: 12 = 2^2 * 3
15 = 3 * 5
16 = 2^4
=> BCNN (12; 15; 16) = 2^4 * 3 * 5 = 240
=> BC (12; 15; 16) = { 240; 480; 720; . . . . .}
=> x thuộc { 240; 480; 720; . . . . .}
Mà 0 < x < 300 => x = 240
x - 2017 = --1 => x - 2017 = 1 => x = 1 + 2017 => x = 2018
a) \(\text{2(x-51)=2.2^2+20}\)
\(2\left(x-51\right)=2.4+20\)
\(2\left(x-51\right)=28\)
\(x-51=28\div2\)
\(x-51=14\)
\(x=14+51\)
\(\text{b)3.(x+1)-26=541}\)
\(3.\left(x+1\right)=541+26\)
\(3\cdot\left(x+1\right)=567\)
\(x+1=567\div3\)
\(x+1=189\)
\(x=189-1\)
\(x=188\)
\(x=65\)
\(\text{c)4(x-3)=7^2-1^10}\)
\(4\left(x-3\right)=49-1\)
\(4\left(x-3\right)=48\)
\(x-3=48\div4\)
\(x-3=12\)
\(x=12+3\)
\(x=15\)
\(\text{e)2x-138=2^3.3^2}\)
\(2x-138=8\cdot9\)
\(2x-138=72\)
\(2x=72+138\)
\(2x=210\)
\(x=210\div2\)
\(x=105\)
\(\text{f)(x-1)^4=16}\)
\(\left(x-1\right)^4=2^4\)
\(x-1=2\)
\(x=2+1\)
\(x=3\)
a) 22.23.x=82
22.23.x= 26
25.x = 26
x = 26:25
x = 2
b) 5x-1.52= 252
5x-1.52 = 54
5x-1 = 54: 52
5x-1 = 52
=> x-1=2
x = 2+1
x = 3
c)(2x-1)3=125
(2x-1)3= 53
=> 2x-1=5
2x = 5+1
2x = 6
x = 6:2
x = 3
d) 8x.2x=44
(8.2)x= 44
16x = 44
16x = 256
16x = 162
=> x=2
e) (x2.53)2 = 56
x2.2. 53.2= 56
x4 . 56 = 56
x4 = 56:56
x4 = 50
x4 =1
=> x=1
a) pt <=> \(\frac{x\left(x+1\right)}{2}=500500\)
<=> \(x^2+x=1001000\)
<=> \(x^2-1000x+1001x-1001000=0\)
<=> \(\left(x-1000\right)\left(x+1001\right)=0\)
<=> \(\orbr{\begin{cases}x=1000\\x=-1001\end{cases}}\)
Do \(x>0\)=> \(x=1000\)
b)
<=> \(2x=210\)
<=> \(x=105\)
c)
<=> \(6x-81=3.7\)
<=> \(x=17\)
d)
<=> \(125-5\left(3x-1\right)=5^2\)
<=> \(5\left(3x-1\right)=100\)
<=> \(3x-1=20\)
<=> \(x=7\)
e)
<=> \(4^{x+1}+1=65\)
<=> \(4^{x+1}=64\)
<=> \(x+1=3\)
<=> \(x=2\)
j)
<=> \(2\left(2x-3\right)=14\)
<=> \(2x-3=7\)
<=> \(x=5\)
Bài 1 . Tìm x
a) 723 - ( 7x - 152 ) = 714
7x - 152 = 723 - 714
7x - 152 = 9
7x = 9 + 152
7x = 161
x = 161 : 7
x = 23
Vậy x = 23
b) ( 2x - 130 ) : 4 + 213 = 52 + 193
( 2x - 130 ) : 4 + 213 = 218
( 2x - 130 ) : 4 = 218 - 213
( 2x - 130 ) : 4 = 5
2x - 130 = 5 . 4
2x - 130 = 20
2x = 20 + 130
2x = 150
x = 150 : 2
x = 75
Vậy x = 75
c) ( x - 6 )2 = 9
( x - 6 )2 = 32
x - 6 = 3 <=> x = 3 + 6 <=> x = 9
x - 6 = -3 <=> x = -3 + 6 <=> x = 3
2x - 138 = 23 . 32
=> 2x - 138 = 72
=> 2x = 72 + 138
=> 2x = 210
=> x = 105
10 + 2x = 43 . 42
10 + 2x =1024
2x = 1024 - 10
2x = 1014
x = 507
(3x - 24) . 73 = 2.74
3x - 24 = 2 . 74 : 73
3x - 16 = 14
3x = 14 + 16
3x = 30
x = 10
x4 = 16
=> x4 = 24
=> x = 2